Confluence of Cellular Degradation Pathways During Interdigital Tissue Remodeling in Embryonic Tetrapods - Montero, Juan A.; Lorda-Diez, Carlos I.; Hurle, Juan M. (Frontiers in Cell and Developmental Biology, 2020)
Digits develop in the distal part of the embryonic limb primordium as radial prechondrogenic condensations separated by undifferentiated mesoderm. In a short time interval the interdigital mesoderm undergoes massive degeneration to determine the formation of free digits. This fascinating process has often been considered as an altruistic cell suicide that is evolutionarily-regulated in species with different degrees of digit webbing. Initial descriptions of interdigit remodeling considered lysosomes as the primary cause of the degenerative process. However, the functional significance of lysosomes lost interest among researcher and was displaced to a secondary role because the introduction of the term apoptosis. Accumulating evidence in recent decades has revealed that, far from being a unique method of embryonic cell death, apoptosis is only one among several redundant dying mechanisms accounting for the elimination of tissues during embryonic development. Developmental cell senescence has emerged in the last decade as a primary factor implicated in interdigit remodeling. Our review proposes that cell senescence is the biological process identified by vital staining in embryonic models and implicates lysosomes in programmed cell death. We review major structural changes associated with interdigit remodeling that may be driven by cell senescence. Furthermore, the identification of cell senescence lacking tissue degeneration, associated with the maturation of the digit tendons at the same stages of interdigital remodeling, allowed us to distinguish between two functionally distinct types of embryonic cell senescence, “constructive” and “destructive”.